2002
DOI: 10.1021/ja025602s
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Deuterium Isotope Effects on Benzylic Hydroxylation by Tyrosine Hydroxylase

Abstract: Tyrosine hydroxylase (TyrH) is a mononuclear, non-heme iron monooxygenase that catalyzes the pterin-dependent hydroxylation of tyrosine to dihydroxyphenylalanine. When 4-methylphenylalanine is used as a substrate for TyrH, 4-hydroxymethylphenylalanine is one of the amino acid products. To examine the mechanism of benzylic hydroxylation, the products and their isotopic compositions were determined with 4-methylphenylalanines containing a mono-, di-, or trideuterated methyl group as substrates. Intrinsic primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
(21 reference statements)
3
32
0
Order By: Relevance
“…Only in the case of benzylic hydroxylation by TyrH has the mechanism been investigated in detail. Analysis of the products when 4-methylphenylalanine containing one, two, or three deuterium atoms in the methyl group was used as a substrate allowed determination of the intrinsic primary and secondary deuterium isotope effects for the hydroxylation step (89). The secondary isotope effect of 1.2 demonstrated that there is significant rehybridization of the methyl carbon in the transition state for hydroxylation; such a result is most consistent with the formation of a benzylic radical intermediate by abstraction of a hydrogen atom from the methyl group by the electrophilic Fe (IV)O species, followed by radical rebound of a hydroxyl radical to form the hydroxylated product (Scheme 6).…”
Section: Methodsmentioning
confidence: 99%
“…Only in the case of benzylic hydroxylation by TyrH has the mechanism been investigated in detail. Analysis of the products when 4-methylphenylalanine containing one, two, or three deuterium atoms in the methyl group was used as a substrate allowed determination of the intrinsic primary and secondary deuterium isotope effects for the hydroxylation step (89). The secondary isotope effect of 1.2 demonstrated that there is significant rehybridization of the methyl carbon in the transition state for hydroxylation; such a result is most consistent with the formation of a benzylic radical intermediate by abstraction of a hydrogen atom from the methyl group by the electrophilic Fe (IV)O species, followed by radical rebound of a hydroxyl radical to form the hydroxylated product (Scheme 6).…”
Section: Methodsmentioning
confidence: 99%
“…39 Siebrand and Smedarchina 149 have suggested that the rate constants and their T dependence reflect the influence of kinetic steps prior to the proton transfer. 150 tyrosine hydroxylase, 290 andyeastalcoholdehydrogenase(YADH). 16,67,74,96 Large KIEs have also been reported for the xylene hydroxylation by cytochrome P-450 291 and dopamine ÎČ-monooxygenase.…”
Section: Survey Of Tunneling Systemsmentioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63] In the catalytic cycle of these enzymes an Fe(IV)=O moiety has been proposed to act as an electrophile toward the aromatic substrate. [55,63,64] In a model study of functional relevance to these enzymes, it was found that treatment of an acetonitrile solution of 4 (Figure 3(a)) with t BuOOH (3 eq) under an argon atmosphere results in the oxidative hydroxylation of the ligand phenyl ring (Scheme 2). [23,35] To isolate the final product of this reaction, base (NEt 3 ) and NaBPh 4 were added in wet methanol, which resulted in the deposition of [(6-C 6 [35] decays over a period of $ 4 hours at À60 C to give a second intermediate prior to the formation of 37.…”
Section: Bioinorganic Chemistry Of Aryl-appended Tris(2-pyridylmethylmentioning
confidence: 99%